Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan Plasa Telkom Rantauprapat, Labuhan Batu - Fakhrozaldi, M. Nicky; Batubara, Beby Masitho; Angelia, Nina (Mahesa Research Center, 2025)
This study aims to analyze the influence of service quality on customer satisfaction of PT Telkom Indonesia (Persero) Tbk in the Labuhan Batu Regency area, with a case study on customers of Plasa Telkom Rantauprapat. In the modern era, technology has become a staple that encourages digital-based services to grow. This study uses a quantitative method with simple linear regression analysis through the SPSS version 25 application. The results of the study show that service quality has a positive and significant effect on customer satisfaction. The regression coefficient value of 0.042 shows that every one-unit increase in service quality will increase customer satisfaction by 4.2%. In addition, the calculated t-value of 14.283 is greater than the t-table of 1.662, and the significance value is 0.000 < 0.05, indicating that the hypothesis is accepted. This means that the higher the quality of the service provided, the higher the customer satisfaction felt. On the other hand, if the quality of service decreases, then the level of customer satisfaction will also decrease.